RELAÃ‡ÃƒO DA MOSCA DOS ESTÃBULOS ð˜šð˜µð˜°ð˜®ð˜°ð˜¹ð˜ºð˜´ ð˜¤ð˜¢ð˜ð˜¤ð˜ªð˜µð˜³ð˜¢ð˜¯ð˜´ (L.) (DIPTERA: MUSCIDAE) COM O PARASITÃ“IDE PUPAL ð˜šð˜±ð˜¢ð˜ð˜¢ð˜¯ð˜¨ð˜ªð˜¢ ð˜¦ð˜¯ð˜¥ð˜ªð˜¶ð˜´ WALKER (HYMENOPTERA: PTEROMALIDAE) - Dias, F. H.N. F.; Chaves, L. E. L.; Berti Filho, E. (REVISTA DE AGRICULTURA, 2020)
RELAÃ‡ÃƒO DA MOSCA DOS ESTÃBULOS ð˜šð˜µð˜°ð˜®ð˜°ð˜¹ð˜ºð˜´ ð˜¤ð˜¢ð˜ð˜¤ð˜ªð˜µð˜³ð˜¢ð˜¯ð˜´ (L.) (DIPTERA: MUSCIDAE) COM O PARASITÃ“IDE PUPAL ð˜šð˜±ð˜¢ð˜ð˜¢ð˜¯ð˜¨ð˜ªð˜¢ ð˜¦ð˜¯ð˜¥ð˜ªð˜¶ð˜´ WALKER (HYMENOPTERA: PTEROMALIDAE)